2018
DOI: 10.1002/bkcs.11499
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Isomerization of Maleic Acid to Fumaric Acid without Catalyst

Abstract: Fumaric acid is an important food additive and industrial intermediate compound. The traditional methods of producing fumaric acid were catalyzed by maleic acid isomerization. In this study, isomerization of maleic acid in water without catalyst was investigated at elevated temperature, which addressed the problem of sewage discharge. HPLC analysis showed maleic acid converted into fumaric acid and small amount of malic acid simultaneously. The effects of concentration of maleic acid, reaction temperature, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…3, vanillic acid is firstly oxidised to oand p-quinones, which react with free radicals to produce ring-opening reactions, obtaining maleic acid. Maleic acid is isomerised to fumaric acid if heated at 120 • C in aqueous solution (Whelan, 1994), producing malic acid at higher temperatures (Gao et al, 2018). This observation indicates that during the transition of maleic to fumaric acid, the double bond is more labile to be hydroxylated, explaining why at higher temperatures malic and tartaric acids were present at higher amounts, especially after several minutes of reaction.…”
Section: Effect Of Reaction Time In C 4 -Dca Production Under Alkalinmentioning
confidence: 99%
“…3, vanillic acid is firstly oxidised to oand p-quinones, which react with free radicals to produce ring-opening reactions, obtaining maleic acid. Maleic acid is isomerised to fumaric acid if heated at 120 • C in aqueous solution (Whelan, 1994), producing malic acid at higher temperatures (Gao et al, 2018). This observation indicates that during the transition of maleic to fumaric acid, the double bond is more labile to be hydroxylated, explaining why at higher temperatures malic and tartaric acids were present at higher amounts, especially after several minutes of reaction.…”
Section: Effect Of Reaction Time In C 4 -Dca Production Under Alkalinmentioning
confidence: 99%
“…However, the catalysts exhibited significantly different MA conversion and SA selectivity owing to the difference in the properties of the Al 2 O 3 support. It has been reported that the isomerization of MA to FA can occur without a catalyst and is strongly affected by the concentration of maleic acid, the reaction temperature, and the pH of the solution [15]. Al 2 O 3 in the Pd/Al 2 O 3 (900)_pH11.5 catalyst was in the γ phase, which has a large specific surface area and strong acid sites, whereas in the Pd/Al 2 O 3 (1100)_pH7.5 catalyst, it was in the θ + α phase, which has a small specific surface area and weak acid sites.…”
Section: Effect Of Al 2 O 3 Support Properties and Pd Dispersionmentioning
confidence: 99%
“…Organic acids are produced industrially by either fermentation or chemical synthesis (Pinazo et al 2015). The main advantage of synthesis is that the resulting product is usually of high purity and concentrated (Ai and Ohdan 1997;Gao et al 2018). But the high energy demand and the use of expensive catalysts (Sang et al 2019), in some cases toxic, environmentally hazardous reagents (Prikaznov et al 2011;Solmi et al 2019), represent great shortcomings of synthetic methods.…”
Section: Introductionmentioning
confidence: 99%